The Dynamics of Trust in Digital Era Cosmetics: Halal Labeling, Information Quality, and Endorser Credibility on Purchase Intention - Yosefa Laura (PT Literati Global Network, 2026)
Purpose: This study investigates the intricate drivers of purchase intention in the competitive Indonesian cosmetics market, focusing on Scarlett Whitening products. We examine how halal labeling, perceived information quality, and endorser credibility influence purchase intention, with brand trust acting as a crucial mediating variable. Method/approach: Employing a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from 115 Scarlett Whitening product users in Kefamenanu City, Indonesia, using purposive sampling. Cross-sectional survey design with self-administered questionnaires was utilized, and data analysis was conducted using SmartPLS 4.0 with 5,000 bootstrap resamples. Findings: Results reveal that halal labeling (β = 0.334, p < 0.001) and perceived information quality (β = 0.139, p < 0.05) significantly and positively influence purchase intention. Both variables also substantially enhance brand trust (halal labeling: β = 0.473, p < 0.001; information quality: β = 0.197, p < 0.05), which in turn powerfully predicts purchase intention (β = 0.707, p < 0.001). Brand trust significantly mediates the effects of both halal labeling (β_indirect = 0.334, p < 0.001) and information quality (β_indirect = 0.139, p = 0.006) on purchase intention. Conversely, endorser credibility showed no significant impact on either brand trust (β = 0.064, p = 0.052) or purchase intention (β = 0.042, p = 0.058). The model explains substantial variance in brand trust (R² = 0.52) and purchase intention (R² = 0.74). Limitations: Cross-sectional design limits causal inference; geographic specificity (Kefamenanu City) and single-brand focus (Scarlett Whitening) may limit generalizability. Future research should employ longitudinal designs, multi-city sampling, and examine multiple product categories and endorser types to establish temporal precedence and boundary conditions. Implications: Resources should be prioritized toward securing halal certifications and fostering positive online review ecosystems rather than over-investing in celebrity endorsements that may no longer yield significant returns in Muslim-majority emerging markets. Brands should reallocate marketing budgets from expensive celebrity contracts to trust-building initiatives. Contribution: This study demonstrates the primacy of intrinsic trust signals (halal certification and user-generated content) over celebrity marketing in Muslim-majority emerging markets, clarifying mediation mechanisms through which marketing signals operate and identifying boundary conditions for source credibility theory in digital-era consumer contexts.